Size-Dependent Behaviour of Representative Volume Element for Granular Material under Gravity-Induced Stress Gradient - Ruilin Li; Yukun Ji; Jun Chen; Daqing Chen; Shangyue Cai (Advances in Materials Science and Engineering)
Gravity is the primary load source in geotechnical engineering, and its effect becomes extremely important in these cases such as lunar research station construction and in situ resource utilization. However, at the current stage, the study on the effect of gravity-induced stress gradients on the behavior of geomaterials is seriously lacking. In this work, the size-dependent behaviour of representative volume element (RVE) of granular matter under the gravity-induced stress gradient is studied. A homogenization theory is proposed firstly, which homogenizes the granular matter into stress gradient continuum through RVE. Then, numerical triaxial loading for RVEs with various heights and particle sizes is carried out under 0∼10 g gravity. The results show that the size effect and its origination appear to have no obvious influence on isotropic compression. However, the macroscopic shear strength, elastic modulus, and volumetric deformation all show size effect dependence, and the gravity-induced stress gradient leads to significant differences between different originations of size effect. The valence, orientation, and elongation degree of microscopic void cells are further analyzed, which suggests that applying of stress gradient results in the evolution of void cells demonstrates a dependence on both the size effect and its origination. The results indicate that the gravity-induced stress gradient and corresponding size effect should be paid sufficient attention to granular mechanics of terrestrial and off-earth engineering.